Genetic structure and biogeographic history of the Bicknell’s Thrush/ Gray-cheeked Thrush species complex - Fitzgerald, Alyssa M; Weir, Jason; Ralston, Joel; Warkentin, Ian G; Whitaker, Darroch M; J. J. Kirchman (The Auk, 2019)
We examined species limits, admixture, and genetic structure among populations in the Bicknell’s Thrush (Catharus bicknelli)–Gray-cheeked Thrush (C. minimus) species complex to establish the geographic and temporal context of speciation in this group, which is a model system in ecology and a high conservation priority. We obtained mitochondrial ND2 sequences from 186 Bicknell’s Thrushes, 77 Gray-cheeked Thrushes, and 55 individuals of their closest relative, the Veery (C. fuscescens), and genotyped a subset of individuals (n = 72) at 5,633 anonymous single nucleotide polymorphic (SNP) loci. Between-species sequence divergence was an order of magnitude greater than divergence within each species, divergence was dated to the late Pleistocene (420 kbp) based on Bayesian coalescence estimation, and a coalescent model (IMa) revealed almost no gene flow between species based on ND2. SNP data were consistent with mitochondrial results and revealed low levels of admixture among species (3 of 37 Bicknell’s Thrushes, no Gray-cheeked Thrushes, and no Veeries were >2% admixed). Species distribution models projected to the Last Glacial Maximum suggest that Bicknell’s Thrush and Gray-cheeked Thrush resided in primarily allopatric refugia in the late Pleistocene, consistent with the genetic data that support reproductive isolation over an extended period of time. Our genetic data suggest that both species underwent demographic expansions, possibly as they expanded out of Pleistocene refugia into their current ranges. We conclude that Bicknell’s Thrush and Gray-cheeked Thrush are 2 distinct species-level lineages despite low levels of Gray-cheeked Thrush introgression in Bicknell’s Thrushes, and divergence has been maintained by a long history of allopatry in subtly different habitats. Their unique phylogeography among boreal forest birds indicates that either cryptic species breaks in eastern North America are still undiscovered, or another factor, such as divergent natural selection, high migratory connectivity, or interspecific competition, played a role in their divergence.
Keywords: Bicknell’s Thrush; Biogeography; boreal forest; Catharus; genetic structure; Gray-cheeked Thrush; phylogeography; Pleistocene; Speciation; species limits